Anodal transcranial direct current stimulation sustainably increases EEG alpha activity in patients with schizophrenia. Issue 3 (18th June 2022) - Pross, Benjamin; Strube, Wolfgang; Papazova, Irina; Güler, Duygu; Häckert, Jan; Keeser, Daniel; Padberg, Frank; Siamouli, Melina; Falkai, Peter; Hasan, Alkomiet
Abstract: Aims: Transcranial direct current stimulation (tDCS) applied to the prefrontal cortex has been frequently used to elicit behavioral changes in patients with schizophrenia. However, the interaction between prefrontal tDCS and electrophysiological changes remains largely uncharted. The present study aimed to investigate cortical electrophysiological changes induced by tDCS in frontal areas by means of repeated electroencephalography (EEG) in patients with schizophrenia. Methods: In total, 20 patients with schizophrenia received 13 minutes of anodal tDCS (1 mA) applied to the left dorsolateral prefrontal cortex (DLPFC). Repeated resting EEG was recorded before (once) and following (at five follow‐up time‐bins) tDCS to trace post‐tDCS effects. We used sLORETA for source reconstruction to preserve the localization of brain signals with a low variance and to analyze frequency changes. Results: We observed significant changes after the stimulation in areas highly connected with the stimulated DLPFC areas. The alpha 1 (8.5‐10.0 Hz) activity showed a highly significant, long‐lasting, increase for up to 1 hour after the stimulation in the postcentral gyrus (Brodmann area 2, 3, and 40). Significant yet unstable changes were also seen in the alpha‐2 frequency band precentral at 10 minutes, in the beta‐1 frequency band occipital at 20 minutes, and in the beta‐3 frequency band temporal at 40 minutes. Conclusion: We were able to show that anodal tDCS can induce stable EEG changes in patients with schizophrenia. The results underline the potential of tDCS to induce long‐lasting neurophysiological changes in patients with schizophrenia showing the possibility to induce brain excitability changes in this population.